Influencing Factors of Health-Related Quality of Life in Thai Children with Cancer - Khamchan, Pranee; Punthmatharith, Busakorn; Petpichetchian, Wongchan; Chotsampancharoen, Thirachit (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
Identification of factors predicting health-related quality of life (HRQOL) is essential to develop effective interventions for nurse in order to improve HRQOL in children with cancer in Thailand. The descriptive study aimed to examine the influences of family functioning, coping, symptom distress, trait anxiety, state anxiety, functional status, and self-care behavior on HRQOL of children with cancer. Purposive sampling was used to recruit 199 children with cancer and 199 caregivers from eight tertiary hospitals in three parts of Thailand. Children were 9-18 years old, received chemotherapy at least one cycle, had good consciousness, and had no serious conditions. The eight self-report questionnaires were used to collect the data: 1) Demographic data questionnaire, 2) Chulalongkorn Family Inventory, 3) The Play-Performance Scale for Children, 4) The Thai Pediatric Quality of Life Inventory version 4.0, 5) The Thai version of Coping of Disease Inventory, 6) The revised Thai versions of State and Trait Anxiety Inventory for Children, 7) Self-care Behavior Questionnaire, and 8) The Memorial Symptom Assessment Scale 10–18. Caregivers self-reported the first three questionnaires and children self-reported the Questionnaires 4-8. Questionnaires 2, 4-5, and 7-8 were tested for reliability using Cronbach’s alpha coefficient; yielding values of .89, .93, .88, .82, and .91 respectively. The reliability of the Questionnaire 6, yielding the Cronbach’s alpha coefficient of .89 for A-State scale and .88 for A-Trait scale. The test-retest intraclass correlation coefficient for Questionnaire 3 was .93. Descriptive statistics and multiple stepwise regression were used for data analysis. The results revealed that 33.3 percent of the variance (R2 = .333, p < .001) of the HRQOL of Thai children with cancer was explained by trait anxiety (β = -.391, p < .001) and functional status (β = .347, p < .001). This provides useful information for nurses to promote functional status of children, thereby in enhancing optimal HRQOL in Thai children with cancer.